Linguistic and sociocultural aspects of translating politically correct lexical units - Kovalova, Olena; Kovalska, Nataliia (My University, 2019)
The article suggests a research into language and sociocultural correlation, and peculiar attention is paid to the term of political correctness. The topic is increasingly relevant due to growing interest to the globalization and integration process between nations, which brings about lexis that involves tolerance towards variety of values, lifestyles and traditions. This tendency is reflected in media texts and should be considered in the process of translation. The article contains examples of politically correct lexical units which were selected from the current English-speaking media resources that illustrate politically correct interpretations in English and Ukrainian.
Keywords: scientific article; translation; politically correct lexical units; linguistic aspect; socio-cultural aspect; наукова стаття; переклад; політкоректні лексичні одиниці; лінгвістичний аспект; соціокультурний аспект; кафедра ділової іноземної мови та міжнародної комунікації